A component of the TOR (Target Of Rapamycin) nutrient-sensing pathway plays a role in circadian rhythmicity in Neurospora crassa. - Lalanthi Ratnayake; Keyur K Adhvaryu; Elizabeth Kafes; Kamyar Motavaze; Patricia Lakin-Thomas (PLoS Genetics)
The TOR (Target of Rapamycin) pathway is a highly-conserved signaling pathway in eukaryotes that regulates cellular growth and stress responses. The cellular response to amino acids or carbon sources such as glucose requires anchoring of the TOR kinase complex to the lysosomal/vacuolar membrane by the Ragulator (mammals) or EGO (yeast) protein complex. Here we report a connection between the TOR pathway and circadian (daily) rhythmicity. The molecular mechanism of circadian rhythmicity in all eukaryotes has long been thought to be transcription/translation feedback loops (TTFLs). In the model eukaryote Neurospora crassa, a TTFL including FRQ (frequency) and WCC (white collar complex) has been intensively studied. However, it is also well-known that rhythmicity can be seen in the absence of TTFL functioning. We previously isolated uv90 as a mutation that compromises FRQ-less rhythms and also damps the circadian oscillator when FRQ is present. We have now mapped the uv90 gene and identified it as NCU05950, homologous to the TOR pathway proteins EGO1 (yeast) and LAMTOR1 (mammals), and we have named the N. crassa protein VTA (vacuolar TOR-associated protein). The protein is anchored to the outer vacuolar membrane and deletion of putative acylation sites destroys this localization as well as the protein's function in rhythmicity. A deletion of VTA is compromised in its growth responses to amino acids and glucose. We conclude that a key protein in the complex that anchors TOR to the vacuole plays a role in maintaining circadian (daily) rhythmicity. Our results establish a connection between the TOR pathway and circadian rhythms and point towards a network integrating metabolism and the circadian system.